The Role of Some Inflammatory Markers (IL-6 and CRP) in the Pathogenesis of Acute Coronary Syndrome in Iraqi CCU for Heart Diseases - Nadia GH. AbdulKarim; Mohamed A. Taher; Amal N. Almarayati (College of Pharmacy University of Baghdad, 2017)
In this work an enzyme linked immunosorbent assay (ELISA) technique has been used for detection of some inflammatory markers in serum of acute coronary syndrome (ACS)-Patients Admitted to the cardiac care unit (CCU) of Iraqi Centre For Heart Diseases and Ibn AlNafees Teaching Hospital. The present method includes quantitative measurement of interleukine-6 (IL-6) and C-reactive protein (CRP), as their increase during symptoms may be responsible for identifying the mechanism of myocardial damag, in addition to their best performance than other quantitative tests perhaps due to their association with atherosclerotic process that belongs to the endothelial dysfunction. Aim of this study is to estimate the prevalence and correlation of IL-6 with CRP in ACS- patients presented with unstable angina/ non-ST elevation myocardial infarction (UA/NSTEMI) symptoms to be as new diagnostic parameters in Iraqi CCU. Seventy (70) ACS- patients with mean age (58.55 year Â±  9.98), from Jun.2009 to Feb. 2010 with diagnosis of UA/NSTEMI were included in this study. Proper history, physical examination, electrocardiograph (ECG), and Echocardiography (ECHO) were performed for all patients in addition to the routine laboratory works including fasting blood glucose, lipid profile, assay of transaminases activity (Aspartate and Alanine transaminase),and biomarkers analysis as cardiac troponin I and T, creatine kinase (CK and CK-MB) and myoglobin. Blood sample was collected from all patients for quantitative assay of IL-6 and CRP. All patients underwent diagnostic coronary angiography, were 66 of them with abnormal coronary outcome and four patients have normal coronary arteries, study include 39- male and 31 female. Seventeen of 67 patients (25.4%) had elevated serum level of IL-6 and fifty four of 62 patients (87.1%) had elevated serum level of CRP. Statistically found strong and significant (SS) correlation between IL-6 and CRP (assessed by Spearman's rho correlation coefficient, P<0.01). The significant proportion of UA/NSTEMI patients that had elevated serum levels of IL-6 and/or CRP, in addition to the strong correlation with coronary angiographic findings make these inflammatory markers to be considered  as risk stratification factors and good predictors for coronary artery disease independent of other traditional risk factors for cardiovascular disease (CVD). Key words: ACS. IL-6. CRP.